Sigmoidovesical fistulas due to complication of colonic diverticular disease - Asiner, Boris; Schenone, Héctor (Cirugía del Uruguay, 1972)
Our experience in the surgical treatment of colovesical fistulas resulting from complications of colonic (sigmoidea!) diverticular disease comprises a series of 10 operated cases in which death-rate and morbility were negligible. Their incidence is 3 % out of a case material comprising 230 cases of diverticular colopathy plus 4 non-hospital cases. Ages were between 42 and 79; 8 were male and 2 female. Surgical tactics require resection of t°he colonic sector with complicated sigmoidea! colonic diverticular disease, including the fistula, with abscission of the fistulized vesical sector whenever such is the case. The addition of prior or concomitant right transverse colostomy (stepped surgery) is advisable. We favour insertion of Folley's catheter for operatory and even post-operatory management.